2017
DOI: 10.1080/10641963.2017.1313853
|View full text |Cite
|
Sign up to set email alerts
|

Berberine promotes ischemia-induced angiogenesis in mice heart via upregulation of microRNA-29b

Abstract: Berberine via upregulation of miR-29b promotes ischemia-induced angiogenesis and improves heart functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…In another example, exosomes derived from miR-126-modified MSCs facilitated the angiogenesis and migration of human umbilical venous endothelial cells after spinal cord injury [53]. Besides, upregulation of miR-29b plays a promotive role in ischemiainduced angiogenesis [54], indicating that miR-29b-3p is a promising factor in the treatment of hypoxic-ischemic brain injury. In this study, we revealed that declining cerebral levels of miR-29b-3p in MCAO rat brain was related to decreased angiogenesis, as indicated by the deregulation of VEGFA, VEGFR2 and CD31.…”
Section: Discussionmentioning
confidence: 99%
“…In another example, exosomes derived from miR-126-modified MSCs facilitated the angiogenesis and migration of human umbilical venous endothelial cells after spinal cord injury [53]. Besides, upregulation of miR-29b plays a promotive role in ischemiainduced angiogenesis [54], indicating that miR-29b-3p is a promising factor in the treatment of hypoxic-ischemic brain injury. In this study, we revealed that declining cerebral levels of miR-29b-3p in MCAO rat brain was related to decreased angiogenesis, as indicated by the deregulation of VEGFA, VEGFR2 and CD31.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is critical for re‐establishing the blood supply to the surviving myocardium after MI and, consequently, to the recovery of cardiac function . To test whether this model is suitable for studying angiogenesis, we detected the angiogenesis by analysis of CD31, which is a biomarker for endothelial cells .…”
Section: Resultsmentioning
confidence: 99%
“…Angiogenesis is critical for re-establishing the blood supply to the surviving myocardium after MI and, consequently, to the recovery of cardiac function. 25 To test whether this model is suitable for studying angiogenesis, we detected the angiogenesis by analysis of CD31, which is a biomarker for endothelial cells. 26 As shown in Figure 6A, ischaemia dramatically induced angiogenesis in mice with MI caused by both traditional method and new method, suggesting this new method is suitable for studying in ischaemia-induced angiogenesis.…”
Section: New Methods Of Mim Surgery Induces Angiogenesismentioning
confidence: 99%
“…Furthermore, the results also demonstrated that the DEGs were correlated with blood vessel morphogenesis and heart development. Previous studies have revealed that angiogenesis plays an essential role in the impaired neovascularization in diabetes (13,14). In addition, effective suppression of the damage of vascular endothelial cells or facilitation of angiogenesis may contribute to the effective treatment of diabetic vascular diseases (15,16).…”
Section: Discussionmentioning
confidence: 99%